Ramp Metering Status in California - Zhongren Wang (International Journal of Transportation Science and Technology, 2013)
The purpose of this paper is to provide an update of the major improvement in terms of ramp metering design and operations in California. These updates include ramp metering policies, ramp metering development plans, ramp metering design manual, and ramp metering and system management initiatives.